Implications of a Biblical Christian Worldview: A Case Study of Sociology, Language, Art, and Pedagogy Lecturers’ Teaching Practices [Implikasi dari Pandangan Dunia Kristen yang Alkitabiah: Studi Kasus Praktik Pengajaran Dosen Sosiologi, Bahasa, Seni, dan Pedagogi] - Siahaan, Meri Fuji (Universitas Pelita Harapan, 2023)
The purpose of this research was to describe lecturers’ practices of integrating a biblical Christian worldview in teaching courses in sociology, Indonesian language, art, and pedagogy (assessment and teaching and learning theories). The participants were the lecturers in one of the education faculties in Tangerang. The data were derived from interviews with five faculty members and collecting their course syllabus. Descriptive qualitative research with a case study approach was employed. The data were described and analyzed in the light of the current literature. The findings showed that those five faculty members have been implementing a biblical Christian worldview in their teaching with a pedagogy of transferring new information. This paper suggests faculty not use a biblical Christian worldview as just intellectual information with a goal of increasing head knowledge but rather use it to reorient students' hearts.